THE DIFFERENCES OF TECHNICAL WORDS IN BRITISH AND AMERICAN ENGLISH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article brings to light, the importance of speaking skills in technical field. The author adopts a communicative approach for the enhancement of speaking skills of her students in the ESP. The researcher focuses on the processes involved in the conversational interaction of the students, thereby conducting such activities in the class which enable her students to be able to use the language appropriate to given social context. The author’s consideration is that the role of the teacher is a technician or an engineer. The teacher's task is to focus the students' attention, and provide exercises to help them develop language facility; however, to ensure their self-reliance, the teacher should only help the students as much as is strictly necessary.